Applicability of excavated rock material: A European technical review implying opportunities for future tunnelling projects - Haas, Maximilian; Mongeard, Laetitia; Ulrici, Luisa; D'Aloia, Laetitia; Cherrey, Agnes; Galler, Robert; Benedikt, Michael (Journal of Cleaner Production, 2021)
The European Organization for Nuclear Research (CERN) is a world-wide leading organisation in the field of particle physics and operation of high-class particle accelerators. Since 2013, CERN has undertaken feasibility investigations for a particle accelerator, named Future Circular Collider (FCC) to be installed within a 90–100 km subsurface infrastructure likely to enter construction phase after 2030. An important aspect of its construction and environmental impact assessment is the management of approximately 9.1 million m 3 of excavated rock and soil. The aim of this paper is to thoroughly review the applications of excavated material across European subsurface construction projects from a technical point of view and set them into context with studies currently ongoing for FCC. We propose a conceptual flow model for rock characterisation with respect to both applicability of excavated material and tunnelling excavation techniques for future international subsurface construction projects. The review has revealed a vast and encouraging potential across different European construction sites efficiently using excavated rock and soil over the past decade ranging from concrete production, geopolymer production, embankment and landfilling. Examples of reviewed subsurface tunnelling projects are likely to be applied for FCC including concrete production, clay-sealing for embankments, geopolymer face stabilization, re-cultivation or agricultural usage as mixed soil material or sustainable waste disposal.
Publisher Copyright: © 2021 Elsevier Ltd
Keywords: Excavated tunnel material; Future circular collider (FCC); Subsurface; Tunnelling